Pengaruh Gaya Hidup, Cita Rasa, dan Citra Merek terhadap Keputusan Pembelian pada Coffee Shop Ruang Bujang Sidoarjo - Firmasyah, Mochammad Fajarudin; Hariasih, Misti (Innovative Technologica: Methodical Research Journal, 2024)
This study aims to determine the influence of lifestyle, taste, and brand image on purchasing decisions at the Ruang Bujang Sidoarjo coffee shop. This study is a descriptive study using the quantitative method. The population used in this study was visitors who had bought at the Coffee Shop of Ruang Bujang Sidoarjo, which amounted to 96 respondents using the accidental sampling technique.. The data analysis technique used in this study was multiple linear regression analysis using the SPSS version 25 for the Window program. The results of this study show : 1) that Lifestyle has a significant effect on Purchasing Decisions, 2) Taste has a significant effect on Purchasing Decisions, 3) Brand Image has a significant effect on purchasing decisions.